The Finance of Unemployment Compensation and its Consequence for the Labor Market - Audrey Guo; Andrew C. Johnston (Institute of Labor Economics (IZA), 2020)
For every payment, there is an equal and opposite tax. In the study of unemployment insurance, economists have developed a substantial literature considering the impact of payments on labor supply. In contrast, they have usually left unexamined the influence on labor demand of the unique tax that finances it. Experience rating in unemployment insurance presents several fascinating questions for economists. This paper marks some of those questions and helps analysts engage them by explaining the unique institutions at play.
Keywords: D22; H22; H25; H71; J23; J32; J38; J65; 330; unemployment insurance; payrol taxation; experience rating